1999
DOI: 10.1126/science.283.5405.1176
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Structure of a Recombinant Gap Junction Membrane Channel

Abstract: Gap junction membrane channels mediate electrical and metabolic coupling between adjacent cells. The structure of a recombinant cardiac gap junction channel was determined by electron crystallography at resolutions of 7.5 angstroms in the membrane plane and 21 angstroms in the vertical direction. The dodecameric channel was formed by the end-to-end docking of two hexamers, each of which displayed 24 rods of density in the membrane interior, which is consistent with an alpha-helical conformation for the four tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
413
0
15

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 515 publications
(454 citation statements)
references
References 40 publications
26
413
0
15
Order By: Relevance
“…Twodimensional projection maps at 7 Å resolution revealed superimposed α-helices that could only arise if the connexons are rotationally staggered by 30° around the 6-fold symmetry axis [5] ( Figure 1a). Thereafter, a 3D map at 7.5 Å in-plane resolution showed that each connexon contains 24 rod-like densities readily interpreted as transmembrane α-helices [7] (Figure 1). The primary sequence identity of each transmembrane helix could not be assigned at this resolution, so they were arbitrarily designated A, B, C and D (Figure 2).…”
Section: The Connexon Contains a Ring Of 24 α-Helicesmentioning
confidence: 99%
See 4 more Smart Citations
“…Twodimensional projection maps at 7 Å resolution revealed superimposed α-helices that could only arise if the connexons are rotationally staggered by 30° around the 6-fold symmetry axis [5] ( Figure 1a). Thereafter, a 3D map at 7.5 Å in-plane resolution showed that each connexon contains 24 rod-like densities readily interpreted as transmembrane α-helices [7] (Figure 1). The primary sequence identity of each transmembrane helix could not be assigned at this resolution, so they were arbitrarily designated A, B, C and D (Figure 2).…”
Section: The Connexon Contains a Ring Of 24 α-Helicesmentioning
confidence: 99%
“…While there must be some structural differences to account for different limiting pore diameters and charge selectivities, it would be truly remarkable if the fundamental organization and packing of the transmembrane helices were different. More to the point, the transmembrane densities derived from cryo-EM of the M34A mutant of Cx26 [9] are virtually identical to those derived from cryo-EM of Cx43 [7].…”
Section: Regions In Nt M1 E1 And/or M3 Have Been Implicated In Linimentioning
confidence: 99%
See 3 more Smart Citations